(untitled) (Actualizaciones en Sida e Infectología, 2024)
Morganella morganii is a Gram-negative facultative anaerobic bacillus, which belongs to human gut commensal microbiota that can adquire resistance to multiple antibiotcs. We report here the isolation of blaKPC positive Morganella morganii isolate from a single patient and the concomitant clinical boarding and description. We present the clinical, microbiological and molecular caracterization of a brain abscess due KPC-producing Morganella morganii and the treatment applied.